Animal-derived surfactants for the treatment and prevention of neonatal respiratory distress syndrome: summary of clinical trials - J Wells Logan; Fernando R Moya (Dove Medical Press, 2009)
J Wells Logan, Fernando R MoyaDepartment of Neonatology, Southeast Area Health Educational Center, New Hanover Regional Medical Center, Wilmington, NC, USAIntroduction: Available literature suggests that the advantage of animal-derived surfactants over first-generation synthetic agents derives from the presence of surface-active proteins and their phospholipid content. Here we summarize the results of clinical trials comparing animal-derived surfactant preparations with other animal-derived surfactants and with both first- and second-generation synthetic surfactants.Methods: Published clinical trials of comparisons of animal-derived surfactants were summarized and compared. Comparisons emphasized differences in (1) key surfactant components attributed with efficacy and (2) differences in published outcomes.Results: For the most important outcomes, mortality and chronic lung disease, currently available natural surfactants are essentially similar in efficacy. When examining secondary outcomes (pneumothorax, ventilator weaning, and need for supplemental oxygen), it appears that both calfactant and poractant have an advantage over beractant. The weight of the evidence, especially for study design and secondary outcomes, favors the use of calfactant. However, the superiority of poractant over beractant, when the higher initial dose of poractant is used, strengthens the case for use of poractant as well.Conclusions: Clinical trials suggest that the higher surfactant protein-B content in calfactant, and perhaps the higher phospholipid content in poractant (at higher initial dose), are the factors that most likely confer the observed advantage over other surfactant preparations. Keywords: surfactant, respiratory distress syndrome, phospholipids, surfactant proteins, chronic lung disease, bronchopulmonary dysplasia